Determinants of the use of family planning services among sexually active adolescents and young women in the Mweka Health Zone, Democratic Republic of the Congo - Woto, Luatala S.; Manenga, Mekanda J.; Ngalula, Kapajika R.; Nkongolo, Kundu M.; Koto-Te-Nyiwa Ngbolua, Jean-Paul; Mukandu, Basua Babintu Leyka; Omanyondo, Marie-Claire Ohambe (Orapuh Journal, 2024)
IntroductionThe low utilization of family planning services among sexually active adolescents and young women is a pressing public health issue, particularly in the Mweka Health Zone of the Democratic Republic of Congo. Understanding the factors influencing this utilization is crucial for improving access and outcomes.PurposeThis study aims to identify the determinants associated with the use of family planning services among sexually active adolescents and young women in the Mweka Health Zone.MethodsThis cross-sectional study surveyed 422 randomly selected adolescents and young women using a prospective survey method supported by a closed-ended, self-administered questionnaire.ResultsKey findings indicate that spousal involvement (χ² = 4.175, p = 0.041), interpregnancy spacing (χ² = 16.364, p = 0.000), and health area affiliation (χ² = 12.396, p = 0.030) significantly influenced the use of family planning services. Stigmatization also negatively impacted service utilization (χ² = 5.05, p < 0.05). Additionally, the duration of walking to access services (χ² = 10.987, p = 0.01) and the alignment of contraceptive methods with expressed needs (χ² = 6.132, p < 0.05) were identified as significant factors.ConclusionBarriers such as limited spousal support, community stigma, inadequate knowledge, and fear of side effects significantly hinder access to family planning services among sexually active adolescents and young women in the Mweka Health Zone. Addressing these barriers is crucial to enhancing service utilization and improving reproductive health outcomes. Potential interventions include increasing community education to reduce stigma, engaging male partners through targeted awareness programs, and improving access to youth-friendly counselling. These strategies could support informed family planning choices, thereby reducing unintended pregnancies and advancing health equity among young women. Further research and policy initiatives are recommended to tailor family planning services to the needs of this demographic.